Strategi pemasaran bank untuk meningkatkan penetrasi pasar di era teknologi - Syaikhu, Raushan Fikri (Maliki Interdisciplinary Journal, 2025)
The bank's marketing strategy in the era of digital technology plays an important role in increasing market penetration and attracting new customers. The use of technology such as mobile banking and Internet banking expands the accessibility of banking services while improving operational efficiency. Relevant product innovation, aggressive digital promotion strategies, and market diversification are the main factors in facing fierce competition in the banking industry. The results show that the integration of digital technology in banking services is able to strengthen customer loyalty and increase competitiveness. Strategic collaboration with business partners and optimal use of technology has proven to be effective in achieving wider market penetration.